Challenges in Intensive Care Management of a Patient with Retropharyngeal Abscess and Mediastinal Extension: A Case Report - Kahar, Liliriawati Ananta (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Retropharyngeal abscess (RPA) is a serious infection of the deep neck space that can extend to the mediastinum, leading to life-threatening complications. This case report highlights the challenges in managing a patient with RPA and mediastinal extension in the intensive care unit (ICU). Case presentation: A 44-year-old male with a history of diabetes mellitus presented with pain, difficulty opening the mouth, and fever. Imaging revealed a retropharyngeal abscess extending to the mediastinum. The patient underwent surgical drainage and was admitted to the ICU for postoperative management. Challenges encountered included airway management, hemodynamic instability, sepsis, and ventilator weaning. The patient required a multidisciplinary approach involving anesthesiologists, intensivists, infectious disease specialists, and surgeons. Conclusion: RPA with mediastinal extension is a challenging condition requiring prompt diagnosis, aggressive treatment, and meticulous intensive care management. A multidisciplinary approach is crucial for successful outcomes.